Role of Standard Operational Procedures (SOP) in Organ Transplant Institution For Transplant Law Enforcement in Indonesia - Bobi Yohanes Sewow (Journal Equity of Law and Governance, 2023)
The demand for human organs without an increase in supply poses a problem for many countries, particularly those where organ donation arrangements are not well regulated, as the risks of organ trafficking increase. It is not always easy to judge among donations that are actually donated under psychological stress or with the expectation of financial or other imbalance. Such a situation can be minimized if communication related to transplantation between the donor and recipient is well established. Transplant-related violations sanctions in general can be ethical, disciplinary or civil, criminal and administrative sanctions.The implementation of Standard Operating Procedures (SOP) of Organ Transplants in each hospital may be different, but there are some basic things and stages that must be considered in carrying out a transplant. In some countries, the existence of donor bureau/institution that regulate organ transplants, really helps minimize the problems that arise. The type of research used is normative juridical research, which is research conducted by conducting an in-depth study of the laws and regulations relating to the problems that are the object of research.